2021
DOI: 10.1177/00332941211006343
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Frames on Personal Narratives of Bullying Memories

Abstract: Research demonstrates the malleability of memory; a dynamic process that occurs across development and can be influenced by internal and external frames. Narratives of past experiences represent one modality of understanding how memories are influenced by these frames. The present experimental study examines how memories of bullying are affected by two distinct yet common cultural frames. College students ( n = 92) were randomly assigned to one of two groups; one with a definition of bullying framing the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…First, interviews and diaries provide insights into certain aspects of life only, while others are omitted. Moreover, it was shown that the interview frame (positive/negative) could influence the sentiment of personal narrative about bullying experiences and its content (Stark et al, 2021). In this regard, our qualitative findings could be further researched using statistical methods such as structural equation modeling.…”
Section: Limitationsmentioning
confidence: 85%
See 1 more Smart Citation
“…First, interviews and diaries provide insights into certain aspects of life only, while others are omitted. Moreover, it was shown that the interview frame (positive/negative) could influence the sentiment of personal narrative about bullying experiences and its content (Stark et al, 2021). In this regard, our qualitative findings could be further researched using statistical methods such as structural equation modeling.…”
Section: Limitationsmentioning
confidence: 85%
“…We included the translated from Russian version of the interview guide in Supplementary Appendix. These interviews intentionally did not include questions about bullying to provide more ecologically valid information about the presence and meaning of bullying in the girls' lives (Stark et al, 2021). The average interview duration was 67 min (S.D.…”
Section: Methodsmentioning
confidence: 99%